Enterprise Surveys : Chad Country Profile 2018 - World Bank (World Bank, Washington, DC, 2018)
The Enterprise Surveys (ES) focus on many aspects of the business environment. These factors can be accommodating or constraining for firms and play an important role in whether an economy’s private sector will thrive or not. Questions contained in the ES aim at covering most of the topics mentioned above. The topics include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, access to finance, innovation, labor, and perceptions about obstacles to doing business. This document summarizes the results of the Enterprise Survey for Chad. Business owners and top managers in 153 firms were interviewed between February to April 2018. The report provides a description of the sample breakdown across the three survey design categories: business sector, firm size, and location.